Balkan dialogues: negotiating identity between prehistory and the present - Gori, Maja; Ivanova-Bieg, Maria (Taylor and Francis, 2017)
Cover -- Title -- Contents -- List of figures -- List of tables -- Notes on contributors -- Balkan dialogues: Negotiating identity between prehistory and the present -- PART I Rethinking groups and cultures -- 1 Later Balkan prehistory: A transcultural perspective -- 2 Ethnicity as a form of social organization: Notes on the multiplicity of understandings of a contested concept -- 3 The transitions between Neolithic and Early Bronze Age in Greece, and the "Indo-European problem" -- 4 Let's stop speaking "cultures"! Alternative means to assess historical developments in the prehistoric Balkans -- 5 A tradition in nine maps: Un-layering Niger River polychrome water jars -- PART II Identities in transition -- 6 Socio-spatial organisation and early Neolithic expansion in Western Anatolia and Greece -- 7 Negotiating identities and exchanging values: Neolithic pottery production and circulation in Thessaly -- 8 Inheritance, population development and social identities: Southeast Europe 5200-4300 BCE -- 9 Culinary landscapes and identity in prehistoric Greece: An archaeobotanical exploration -- PART III Frontiers and boundaries -- 10 Neolithic assemblages and spatial boundaries as exemplified through the Neolithic of Northwestern Turkey -- 11 Cultivating identities: Landscape production among early farmers in the Southern Balkans -- 12 Erasing boundaries or changing identities? The transition from Early/Middle to Late Neolithic, new evidence from Southern Serbia -- 13 Practicing archaeology and researching present identities in no man's land: A view from the Tri-National Prespa Lake -- Index
Keywords: Aufsatzsammlung; Konferenzschrift -- 02.05.2014-03.05.2014 -- Heidelberg; Bronzezeit; Neolithikum; Funde; Siedlung; Archäologie; Balkanhalbinsel; Ethnologie